Highly cross-linked polyethylene in total hip arthroplasty, present and future - Mori, Toshiharu; Tsukamoto, Manabu (Annals of Joint; Vol 3 (August 2018): Annals of Joint, 2018)
Excessive polyethylene wear after total hip arthroplasty using non-cross-linked ultra-high-molecular-weight polyethylene (UHMWPE) is known to cause osteolysis followed by implant loosening (1,2). To reduce the amount of wear, several manufacturers have attempted to modify bearing surface materials. Highly cross-linked polyethylene (HXLPE) was utilized the processes of gamma or electron beam radiation, to increase the degree of crosslinking within the material. Re-melting process would take on to reduce the amount of oxidation involving to crosslink. As a result, it is expected that wear resistance of the polyethylene increase.